HISTORICAL-ARCHITECTURAL COMPLEX BAHAUDDDINA NAKSHBAND (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
In the article Sheikh Bakhauddin Nakshbandi’s Shrine , which attracted the attention of world travelers to Bukhara , its historical structure and issues of Moslems` pilgrimage and prayer are scientifically analyzed via travelers` diaries.